Prevention of Occupational Hazards Among Sanitary Workers: Knowledge, Attitude, and Practice Survey in Bulehora, West Guji Zone, Oromia, Ethiopia - Degavi G; Dereso CW; Shinde S; Adola II SG; Kasimayan P (Dove Medical Press, 2021)
Girish Degavi,1 Chala Wata Dereso,2 Sanjay Shinde,1 Shiferaw Gelchu Adola II,1 Pandiarajan Kasimayan1 1Department of Nursing, College of health and medical science, Bulehora University, Hegremariam, Oromia, Ethiopia; 2Bulehora University, Hegremariam, Oromia, EthiopiaCorrespondence: Girish DegaviDepartment of Nursing, College of health and medical science, Bulehora University, Hegremariam, Oromia, EthiopiaTel +251-966686212Email girishdegavi1984@bhu.edu.etIntroduction: The production of waste is due to the result of commercial activities, consumption, and utilization of products or materials. It is further believed that mainly solid waste includes non-harmful waste which may be from households, mainly kitchens, and even from organizations and institutions, shops and various types of markets, and manufacturing industries. Solid waste handling, management, and accurate and appropriate disposal is a hot topic relating to public and environmental health concerns.Methods: A cross-sectional quantitative study design was incorporated to assess knowledge, attitude, and practice and associated factors regarding prevention of occupational risks and health hazards among sanitary workers in Bulehora University, a government organization in West Guji Zone, Ethiopia. One hundred and ninety-one solid waste handlers found to be working in this institution were included in the study.Results: The response rate of samples in the present study was found to be 94.4%, of which the majority were females, which accounted for 79.7%. The median age of the study samples was 29 years. It was found that 64% of study samples stated good knowledge of the prevention of occupational health risks. About 76.4% of solid waste collectors had a good attitude and only 8.9% showed good practice regarding prevention of occupational health hazards. Job dissatisfaction was found to be a statistically significant factor along with the use of personal protective equipment (PPE) in implementing good practice work patterns among sanitation workers, even though they had been provided with basic personal protective equipment.Conclusion: The study concluded that there is a need for development of plans on implementation of basic occupational health services while enforcing the provision of personal protective equipment and supervising solid waste collectors.Keywords: occupational hazards, sanitary workers, West Guji Zone, Bulehora University